2022
DOI: 10.1186/s40478-022-01499-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of the dentate gyrus reveals semantic dementia specific molecular pathology

Abstract: Semantic dementia (SD) is a clinical subtype of frontotemporal dementia consistent with the neuropathological diagnosis frontotemporal lobar degeneration (FTLD) TDP type C, with characteristic round TDP-43 protein inclusions in the dentate gyrus. Despite this striking clinicopathological concordance, the pathogenic mechanisms are largely unexplained forestalling the development of targeted therapeutics. To address this, we carried out laser capture microdissection of the dentate gyrus of 15 SD patients and 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Furthermore, genome-wide association studies encompassing 4,308 controls and 2,154 clinically diagnosed FTD cases identified a network of 64 risk genes associated with "semantic dementia," a diagnosis strongly correlated with TDP-C. 73 It would be of considerable interest to see whether distinctive expression patterns of these genes can be linked to the ATL of TDP-C cases. Compared with control, AD, and other FTLD datasets, proteomic analyses in 15 patients with TDP-C also found increased cell adhesion proteins of the cadherin-catenin complex at the synaptic junction in samples from TDP-C. 74 However, this analysis was limited to the dentate gyrus, which contains mostly Pick-like round TDP-43 inclusions rather than the thick long dystrophic neurites, making its relevance to the cortical ATL degeneration unclear.…”
Section: Neuropathology Of Tdp-c and Comparison To Other Ftld-tdp Typesmentioning
confidence: 90%
“…Furthermore, genome-wide association studies encompassing 4,308 controls and 2,154 clinically diagnosed FTD cases identified a network of 64 risk genes associated with "semantic dementia," a diagnosis strongly correlated with TDP-C. 73 It would be of considerable interest to see whether distinctive expression patterns of these genes can be linked to the ATL of TDP-C cases. Compared with control, AD, and other FTLD datasets, proteomic analyses in 15 patients with TDP-C also found increased cell adhesion proteins of the cadherin-catenin complex at the synaptic junction in samples from TDP-C. 74 However, this analysis was limited to the dentate gyrus, which contains mostly Pick-like round TDP-43 inclusions rather than the thick long dystrophic neurites, making its relevance to the cortical ATL degeneration unclear.…”
Section: Neuropathology Of Tdp-c and Comparison To Other Ftld-tdp Typesmentioning
confidence: 90%
“…We currently lack a clear answer to these questions. However, SFRP1 has not emerged as a differentially expressed protein in five proteomic studies of the substantia nigra from Parkinson's disease patients 80,81 , nor in the limited studies analysing the brain of individuals with frontotemporal dementia [82][83][84] .…”
Section: Discussionmentioning
confidence: 99%